Zirconia ceramic for ceramic compass pins and preparation method thereof

By adding doping elements to zirconia ceramics and adjusting the preparation process, the problem of zirconia ceramics is solved, and its toughness and bending strength are significantly improved, making it more suitable for use in ceramic compass pins and other applications.

CN119751057APending Publication Date: 2025-04-04ZHEJIANG JINGPENG ZIRCONIUM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411955691.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Zirconia ceramics have high brittleness, poor toughness and bending strength, which leads to prone to breaking and tipping when used incorrectly, and are not resistant to falling and folding.

Method used

By adjusting the formulation and preparation process of zirconia ceramics, doping elements such as yttrium oxide, calcium oxide, chromium oxide, titanium oxide and alumina are added, and ball milling, cold isostatic molding and vacuum sintering are used to improve the toughness and bending strength of the ceramics.

Benefits of technology

It significantly improves the toughness and bending strength of zirconia ceramics, reduces its brittleness, makes it less likely to break the head and fold the tip during use, and is durable to fall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215758580000111
    Figure BDA0005215758580000111
Patent Text Reader

Abstract

The present invention provides a zirconia ceramic for ceramic compass pins and a preparation method thereof, the preparation method comprising: S100, feeding raw materials including zirconia, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, dispersant, and carboxyl organic modifier into a ball mill, using ethanol as a medium, wet milling and mixing uniformly, and taking out to obtain a mixed powder; S200, heating and mixing raw materials including mixed powder, binder and amino organic modifier with ethanol under ultraviolet light conditions to obtain slurry; S300, freeze-drying the slurry, grinding and sieving, obtaining a modified mixed powder; S400, cold isostatic pressing the modified mixed powder to obtain a ceramic blank; S500, feeding the ceramic blank into a sintering device for vacuum sintering to obtain zirconia ceramics. The zirconia ceramics obtained by the present invention have better toughness and bending strength, and are particularly suitable for the manufacture of ceramic compass pins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a zirconia ceramic for ceramic compass pins and a preparation method thereof. Background Art

[0002] Zirconia ceramics are a type of oxide ceramic with broad application prospects. Its crystal structure gives it excellent physical and chemical properties, as well as outstanding mechanical properties. It can also be used as a matrix material for refractory ceramics, dielectric ceramics, and ultra-high temperature structural ceramics.

[0003] In recent years, zirconia ceramic knives are gradually replacing metal knives (such as fruit knives, box cutters, utility knives, etc.), and have been widely used in people's daily lives. In the above application scenarios, the advantages of zirconia ceramics are easy maintenance, no rust, sharp blades, and safety. However, the disadvantages of zirconia ceramic knives are greater brittleness, poor toughness and bending strength.

[0004] In addition to being used in cutting tools, products that use oxide ceramics to replace metal needles or metal cutting tools have also appeared in the prior art. Taking the compass pin as an example, the material of the compass pin is usually made of metal (such as iron, steel, etc.), which has high hardness and durability. The advantage of using oxide ceramics instead of metal as compass pins is that it is more beautiful. However, the disadvantages arising from this are similar to those of zirconia ceramic cutting tools, namely: zirconia ceramics are relatively brittle, not resistant to falling, not resistant to folding, and are prone to breaking and tip folding when used improperly.

[0005] Therefore, how to improve the toughness and flexural strength of oxide ceramics and reduce their brittleness is a technical problem that those skilled in the art need to solve. Summary of the invention

[0006] The problem solved by the invention is how to provide a zirconium oxide ceramic with higher toughness and bending strength and lower brittleness.

[0007] In order to solve at least one of the above problems, the present invention provides a method for preparing zirconia ceramics for ceramic compass pins, the preparation method comprising:

[0008] S100, feeding raw materials including zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, a dispersant, and a carboxyl organic modifier into a ball mill, using ethanol as a medium, wet-milling and mixing to obtain a mixed powder;

[0009] S200, heating and mixing the raw materials including the mixed powder, the binder and the amino organic modifier with ethanol under ultraviolet light to obtain a slurry;

[0010] S300, freeze-drying, grinding and sieving the slurry to obtain a modified mixed powder;

[0011] S400, performing cold isostatic pressing on the modified mixed powder to obtain a ceramic blank;

[0012] S500, sending the ceramic blank into a sintering device for vacuum sintering to obtain the zirconia ceramic.

[0013] In any of the above technical solutions, in S100, the dispersant includes sodium hexametaphosphate.

[0014] In any of the above technical solutions, in S100, the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: dispersant: carboxyl organic modifier = 100: (4-6): (2-3): (1-2): (0.5-1): (0.5-1): (0.5-1): (2-3).

[0015] In any of the above technical solutions, in S200, the binder includes an aluminosilicate binder.

[0016] In any of the above technical solutions, every 100 parts by mass of the aluminosilicate binder includes: 30 parts by mass of sodium silicate; 25 parts by mass of sodium aluminate; 20 parts by mass of kaolin; 8 parts by mass of potassium hydroxide; 8 parts by mass of potassium tetraborate; 6 parts by mass of aluminum hydroxide; and 3 parts by mass of polyacrylamide.

[0017] In any of the above technical solutions, in S300, the freeze drying temperature is -80°C to -45°C, and the drying time is 4h to 8h; and / or in S400, the cold isostatic pressing pressure is 200MPa to 300MPa, and the holding time is 5min to 10min; and / or in S500, the vacuum sintering temperature is 1200°C to 1400°C, the sintering time is 1h to 3h, and the vacuum degree is 0.5×10 -3 Pa to 0.8×10 -3 Pa.

[0018] In any of the above technical solutions, in S200, the mass ratio of mixed powder: binder: amino organic modifier is 100: (2-6): (2-3).

[0019] In any of the above technical solutions, the exposure dose of the ultraviolet light is 1500mJ / cm 2 Up to 1800mJ / cm 2 , the heating temperature is 60°C to 70°C.

[0020] In any of the above technical solutions, the carboxyl organic modifier includes diethylenetriaminepentaacetic acid dianhydride; the amino organic modifier includes dimethylaminoethyl methacrylate.

[0021] The present invention also provides a zirconia ceramic for ceramic compass pins, and the zirconia ceramic is obtained by using the preparation method described in any of the above technical solutions.

[0022] Beneficial Effects

[0023] The present invention provides a method for preparing zirconium oxide ceramics for ceramic compass pins. The preparation method firstly feeds raw materials including zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, a dispersant, and a carboxyl organic modifier into a ball mill, uses ethanol as a medium, wet-mills and mixes them evenly, and obtains a mixed powder after taking it out. Then, the raw materials including the mixed powder, a binder, and an amino organic modifier are heated, mixed, and stirred evenly with ethanol under ultraviolet light to prepare a slurry. Subsequently, the slurry is freeze-dried, ground, and sieved to obtain a modified mixed powder. Finally, the modified mixed powder is cold isostatically pressed to obtain a ceramic blank, and the ceramic blank is fed into a sintering device for vacuum sintering to obtain the zirconium oxide ceramic. Through the above steps, the present invention can obtain zirconia ceramics with better toughness and bending strength, and the zirconia ceramics have low brittleness. When used as ceramic compass pins, they are not easy to break or fold during use, and are also drop-resistant and durable, and are not easy to break when impacted by external forces. Therefore, they are particularly suitable for the manufacture of ceramic compass pins. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.

[0025] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.

[0026] The present invention provides a method for preparing zirconia ceramics for ceramic compass pins. The compass pin is usually installed on one leg of the compass, and its main function is to fix the center of the circle to ensure that the compass does not move during the drawing process, so that a circle of the required size or an arc of a specific curvature can be accurately drawn. The material of the compass pin is usually made of metal (such as iron, steel, etc.). The advantage of using oxide ceramics instead of metal as the compass pin is that it is more beautiful and not easy to rust. However, its disadvantages are: zirconia ceramics are relatively brittle, and are easy to break and break when used improperly (such as pressing hard), and they are easily damaged after being impacted by external forces, and are not resistant to falling or breaking.

[0027] In order to solve the above problems, the present invention adjusts the formula and preparation process of zirconia ceramics to improve its toughness and bending strength and reduce its brittleness. The preparation method of the present invention comprises:

[0028] S100, feeding raw materials including zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, a dispersant, and a carboxyl organic modifier into a ball mill, using ethanol as a medium, wet-milling and mixing to obtain a mixed powder; the dispersant specifically includes sodium hexametaphosphate;

[0029] S200, heating and mixing the raw materials including the mixed powder, the binder and the amino organic modifier with ethanol under ultraviolet light to obtain a slurry; in S200, the binder includes an aluminosilicate binder;

[0030] S300, freeze-drying the slurry, grinding and sieving to obtain a modified mixed powder; the freeze-drying temperature is -80°C to -45°C, and the drying time is 4h to 8h;

[0031] S400, cold isostatic pressing the modified mixed powder to obtain a ceramic blank; the cold isostatic pressing pressure is 200 MPa to 300 MPa, and the holding time is 5 min to 10 min;

[0032] S500, sending the ceramic blank into a sintering device for vacuum sintering to obtain the zirconia ceramic; the vacuum sintering has a sintering temperature of 1200° C. to 1400° C., a sintering time of 1 h to 3 h, and a vacuum degree of 0.5×10 -3 Pa to 0.8×10 -3 Pa.

[0033] Among the above raw materials of S100, yttrium oxide as a doping element can significantly improve the performance of zirconia ceramics. Specifically, adding an appropriate amount of yttrium oxide can improve the wear resistance, high temperature resistance and chemical stability of zirconia ceramics, while also enhancing its fracture toughness, making it tougher and more durable. Among all zirconia materials, yttrium-stabilized zirconia has the highest bending strength, and its fine grain size makes it highly wear-resistant. In addition, the addition of yttrium oxide makes zirconia ceramics denser, with fewer pores, and its mechanical strength, corrosion resistance, and impact toughness are all improved.

[0034] Calcium oxide is one of the more effective doping elements in zirconia ceramics. Adding calcium oxide in zirconia ceramics in an appropriate amount can improve its thermal stability and toughness and reduce its grain size. Calcium oxide-doped zirconia ceramics also have good wear resistance and corrosion resistance. Adding chromium oxide in an appropriate amount can effectively improve the toughness of ceramics. Specifically, chromium oxide mainly works through the following mechanisms: chromium oxide can form dense and uniform grains in ceramics, effectively prevent crack propagation, promote the closure of cracks on the surface microcracks, consume surface stress, alleviate edge effects, and reduce the brittleness of ceramic materials. An appropriate amount of titanium oxide can increase the density of ceramics and reduce the formation of pores. It can also enhance the mechanical properties of zirconia ceramics and improve their strength and toughness. Alumina ceramics have a series of characteristics such as high mechanical strength, wear resistance, and oxidation resistance. Adding alumina to zirconia ceramics is particularly helpful in improving the flexural strength of zirconia ceramics. In summary, raw materials such as yttrium oxide, calcium oxide, chromium oxide, titanium oxide, and aluminum oxide play their respective roles in zirconia ceramics. By adding the above raw materials reasonably, the performance of zirconia ceramics can be significantly improved.

[0035] In some preferred embodiments of the present invention, in S100, the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: dispersant: carboxyl organic modifier = 100: (4-6): (2-3): (1-2): (0.5-1): (0.5-1): (0.5-1): (2-3).

[0036] In a further preferred embodiment of the present invention, in S100, the mass ratio of zirconium oxide:yttrium oxide:calcium oxide:chromium oxide:titanium oxide:aluminum oxide:dispersant:carboxyl organic modifier is 100:5:3:2:1:1:0.5:3.

[0037] It can be understood that the present invention prepares a composite zirconia ceramic material containing a variety of inorganic non-metallic oxide additive components. The addition of the above-mentioned components helps to improve the various properties of zirconia ceramics. However, the addition of multiple components leads to a decrease in the bonding force between various inorganic non-metallic oxides and zirconia materials in the pulping and isostatic pressing processes. This is caused by the interface differences between the raw materials. For small and sharp products such as ceramic compass pins, the above problem will cause microcracks to easily appear on the surface of the product. Therefore, after preparing the mixed powder, the present invention mixes the mixed powder with a binder to prepare a slurry, and then uses the modified mixed powder obtained by freeze-drying the slurry, grinding and screening for cold isostatic pressing. The binder is specifically an aluminosilicate binder, which, as a high-temperature binder, can effectively reduce the interface effect between the components during the sintering process and improve the bonding force between the components.

[0038] Preferably, every 100 parts by mass of the aluminosilicate binder comprises: 30 parts by mass of sodium silicate; 25 parts by mass of sodium metaaluminate; 20 parts by mass of kaolin; 8 parts by mass of potassium hydroxide; 8 parts by mass of potassium tetraborate; 6 parts by mass of aluminum hydroxide; and 3 parts by mass of polyacrylamide.

[0039] In order to further reduce the difference in interfacial properties between the raw materials, improve the bonding strength between the raw materials, and avoid microcracks and defects in the product, the present invention adds a carboxyl organic modifier in the process of preparing the mixed powder, and adds an amino organic modifier in the process of preparing the slurry, and then the mixture is subjected to ultraviolet light and heated stirring in the process of preparing the slurry. The carboxyl organic modifier includes diethylenetriaminepentaacetic acid dianhydride; the amino organic modifier includes dimethylaminoethyl methacrylate. In S200, the exposure dose of the ultraviolet light is 1500mJ / cm 2 Up to 1800mJ / cm 2 , the heating temperature is 60° C. to 70° C. Preferably, in S200, the mixed powder: binder: amino organic modifier is 100: (2-6): (2-3) by mass ratio. Further preferably, in S200, the mixed powder: binder: amino organic modifier is 100: 4: 3 by mass ratio.

[0040] The carboxyl group in diethylenetriaminepentaacetic acid dianhydride and the amino group in dimethylaminoethyl methacrylate undergo condensation reaction and imidization under the conditions of ultraviolet light and heating. Potassium hydroxide in the aluminosilicate binder can catalyze the above reaction. The imidization reaction allows the components in the mixed powder and the binder to be tightly bonded through chemical bonds, thereby improving the product performance.

[0041] Example 1

[0042] This embodiment provides a method for preparing zirconia ceramics for ceramic compass pins, which specifically includes the following steps:

[0043] S1. According to the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: sodium hexametaphosphate: diethylenetriamine pentaacetic acid anhydride = 100: 5: 3: 2: 1: 1: 0.5: 3, zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, sodium hexametaphosphate, and diethylenetriamine pentaacetic acid anhydride are fed into a ball mill, and ethanol is used as a medium to mix them uniformly by wet ball milling. The ball milling speed is 300 r / min, and the ball milling time is 12 h. After taking out, a mixed powder is obtained;

[0044] S2. Dry-grind and mix the above raw materials in a mass ratio of sodium silicate: sodium aluminate: kaolin: potassium hydroxide: potassium tetraborate: aluminum hydroxide: polyacrylamide = 30:25:20:8:8:6:3 to obtain an aluminosilicate binder;

[0045] S3, according to the mass ratio of mixed powder: binder: dimethylaminoethyl methacrylate = 100:4:3, the mixed powder, binder and dimethylaminoethyl methacrylate were mixed with ethanol 2.5 times the mass of the mixed powder at 1800mJ / cm 2 The mixture was heated to 70° C. under ultraviolet light, and mixed and stirred for 30 minutes to prepare a slurry;

[0046] S4, freeze-drying the slurry at -80°C for 6 h, grinding and sieving through a 600-mesh sieve to obtain a modified mixed powder;

[0047] S5, performing cold isostatic pressing of the modified mixed powder at 250 MPa for 8 min to obtain a ceramic blank;

[0048] S6, send the ceramic blank into nitrogen protection and the vacuum degree is 0.5×10 -3 The sintering equipment of Pa was used to carry out vacuum sintering at 1250°C for 1.5 hours to obtain sample 1 of zirconia ceramic.

[0049] Example 2

[0050] This embodiment provides a method for preparing zirconia ceramics for ceramic compass pins, which specifically includes the following steps:

[0051] S1. According to the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: sodium hexametaphosphate: diethylenetriamine pentaacetic acid anhydride = 100:4:2:1:0.5:0.5:0.5:2, zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, sodium hexametaphosphate, and diethylenetriamine pentaacetic acid anhydride are fed into a ball mill, and ethanol is used as a medium to mix them uniformly by wet ball milling. The ball milling speed is 300 r / min, and the ball milling time is 12 h. After taking out, a mixed powder is obtained;

[0052] S2. Dry-grind and mix the above raw materials in a mass ratio of sodium silicate: sodium aluminate: kaolin: potassium hydroxide: potassium tetraborate: aluminum hydroxide: polyacrylamide = 30:25:20:8:8:6:3 to obtain an aluminosilicate binder;

[0053] S3, according to the mass ratio of mixed powder: binder: dimethylaminoethyl methacrylate = 100:2:2, the mixed powder, binder and dimethylaminoethyl methacrylate were mixed with ethanol 2.5 times the mass of the mixed powder at 1600mJ / cm 2The mixture was heated to 70° C. under ultraviolet light, and mixed and stirred for 30 minutes to prepare a slurry;

[0054] S4, freeze-drying the slurry at -80°C for 6 h, grinding and sieving through a 600-mesh sieve to obtain a modified mixed powder;

[0055] S5, performing cold isostatic pressing of the modified mixed powder at 250 MPa for 8 min to obtain a ceramic blank;

[0056] S6, send the ceramic blank into nitrogen protection and the vacuum degree is 0.5×10 -3 The sintering equipment of Pa was used to carry out vacuum sintering at 1300°C for 1.5 hours to obtain sample 2 of zirconia ceramic.

[0057] Example 3

[0058] This embodiment provides a method for preparing zirconia ceramics for ceramic compass pins, which specifically includes the following steps:

[0059] S1. According to the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: sodium hexametaphosphate: diethylenetriaminepentaacetic acid anhydride = 100:6:2:1:1:1:1:2, zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, sodium hexametaphosphate, and diethylenetriaminepentaacetic acid anhydride are fed into a ball mill, and ethanol is used as a medium to mix them uniformly by wet ball milling. The ball milling speed is 300 r / min, and the ball milling time is 12 h. After taking out, a mixed powder is obtained;

[0060] S2. Dry-grind and mix the above raw materials in a mass ratio of sodium silicate: sodium aluminate: kaolin: potassium hydroxide: potassium tetraborate: aluminum hydroxide: polyacrylamide = 30:25:20:8:8:6:3 to obtain an aluminosilicate binder;

[0061] S3, according to the mass ratio of mixed powder: binder: dimethylaminoethyl methacrylate = 100:6:2, the mixed powder, binder and dimethylaminoethyl methacrylate were mixed with ethanol 2.5 times the mass of the mixed powder at 1500mJ / cm 2 The mixture was heated to 60° C. under ultraviolet light, and mixed and stirred for 30 minutes to prepare a slurry;

[0062] S4, freeze-drying the slurry at -60°C for 8h, grinding and sieving through a 600-mesh sieve to obtain a modified mixed powder;

[0063] S5, performing cold isostatic pressing of the modified mixed powder at 200 MPa for 10 min to obtain a ceramic blank;

[0064] S6, send the ceramic blank into nitrogen protection and the vacuum degree is 0.5×10 -3 The sintering equipment of Pa was used to carry out vacuum sintering at 1350°C for 1.5 hours to obtain sample 3 of zirconia ceramic.

[0065] Example 4

[0066] This embodiment provides a method for preparing zirconia ceramics for ceramic compass pins, which specifically includes the following steps:

[0067] S1. According to the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: sodium hexametaphosphate: diethylenetriaminepentaacetic acid anhydride = 100:5:3:1:1:1:1:2.5, zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, sodium hexametaphosphate, and diethylenetriaminepentaacetic acid anhydride are fed into a ball mill, and ethanol is used as a medium to mix them uniformly by wet ball milling. The ball milling speed is 300 r / min, and the ball milling time is 12 h. After taking out, a mixed powder is obtained;

[0068] S2. Dry-grind and mix the above raw materials in a mass ratio of sodium silicate: sodium aluminate: kaolin: potassium hydroxide: potassium tetraborate: aluminum hydroxide: polyacrylamide = 30:25:20:8:8:6:3 to obtain an aluminosilicate binder;

[0069] S3, according to the mass ratio of mixed powder: binder: dimethylaminoethyl methacrylate = 100:5:2, the mixed powder, binder and dimethylaminoethyl methacrylate were mixed with ethanol 2.5 times the mass of the mixed powder at 1700mJ / cm 2 The mixture was heated to 65° C. under ultraviolet light, and mixed and stirred for 30 minutes to prepare a slurry;

[0070] S4, freeze-drying the slurry at -50°C for 8h, grinding and sieving through a 600-mesh sieve to obtain a modified mixed powder;

[0071] S5, performing cold isostatic pressing of the modified mixed powder at 300 MPa for 5 min to obtain a ceramic blank;

[0072] S6, send the ceramic blank into nitrogen protection and the vacuum degree is 0.5×10 -3 The sintering equipment of Pa was used to carry out vacuum sintering at 1250°C for 1.5 hours to obtain sample 4 of zirconia ceramic.

[0073] Comparative Example 1

[0074] This embodiment provides a method for preparing zirconia ceramics for ceramic compass pins, which specifically includes the following steps:

[0075] S1. According to the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: sodium hexametaphosphate = 100: 5: 3: 2: 1: 1: 0.5, zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide and sodium hexametaphosphate are fed into a ball mill, and ethanol is used as a medium to mix them uniformly by wet ball milling. The ball milling speed is 300 r / min, and the ball milling time is 12 h. After taking out, a mixed powder is obtained;

[0076] S2. Dry-grind and mix the above raw materials in a mass ratio of sodium silicate: sodium aluminate: kaolin: potassium hydroxide: potassium tetraborate: aluminum hydroxide: polyacrylamide = 30:25:20:8:8:6:3 to obtain an aluminosilicate binder;

[0077] S3, heating the mixed powder, the binder and ethanol with a mass 2.5 times that of the mixed powder to 70° C. in a mass ratio of mixed powder: binder = 100:4, mixing and stirring for 30 minutes to prepare a slurry;

[0078] S4, freeze-drying the slurry at -80°C for 6 h, grinding and sieving through a 600-mesh sieve to obtain a modified mixed powder;

[0079] S5, performing cold isostatic pressing of the modified mixed powder at 250 MPa for 8 min to obtain a ceramic blank;

[0080] S6, send the ceramic blank into nitrogen protection and the vacuum degree is 0.5×10 -3 The sintering equipment of Pa was used to carry out vacuum sintering at 1250°C for 1.5 hours to obtain sample 5 of zirconia ceramic.

[0081] Comparative Example 2

[0082] This embodiment provides a method for preparing zirconia ceramics for ceramic compass pins, which specifically includes the following steps:

[0083] S1. According to the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: sodium hexametaphosphate = 100: 5: 3: 2: 1: 1: 0.5, zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide and sodium hexametaphosphate are fed into a ball mill, and ethanol is used as a medium to mix them uniformly by wet ball milling. The ball milling speed is 300 r / min, and the ball milling time is 12 h. After taking out, a mixed powder is obtained;

[0084] S2, cold isostatic pressing the mixed powder at 250 MPa for 8 min to obtain a ceramic blank;

[0085] S3, send the ceramic blank into nitrogen protection and the vacuum degree is 0.5×10 -3The sintering equipment of Pa was used to carry out vacuum sintering at 1250°C for 1.5 hours to obtain sample 6 of zirconia ceramic.

[0086] Performance Testing

[0087] The performance test results of the samples obtained in the above examples and comparative examples are listed in Table 1.

[0088] Table 1

[0089]

[0090] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing zirconium oxide ceramics for ceramic compass pins, characterized in that: The preparation method comprises: S100, feeding raw materials including zirconium oxide, yttrium oxide, calcium oxide, chromium oxide, titanium oxide, aluminum oxide, a dispersant, and a carboxyl organic modifier into a ball mill, using ethanol as a medium, wet-milling and mixing to obtain a mixed powder; S200, heating and mixing the raw materials including the mixed powder, the binder and the amino organic modifier with ethanol under ultraviolet light to obtain a slurry; S300, freeze-drying, grinding and sieving the slurry to obtain a modified mixed powder; S400, performing cold isostatic pressing on the modified mixed powder to obtain a ceramic blank; S500, sending the ceramic blank into a sintering device for vacuum sintering to obtain the zirconia ceramic.

2. The preparation method according to claim 1, characterized in that: In S100, the dispersant includes sodium hexametaphosphate.

3. The preparation method according to claim 1, characterized in that: In S100, the mass ratio of zirconium oxide: yttrium oxide: calcium oxide: chromium oxide: titanium oxide: aluminum oxide: dispersant: carboxyl organic modifier = 100: (4-6): (2-3): (1-2): (0.5-1): (0.5-1): (0.5-1): (2-3).

4. The preparation method according to claim 1, characterized in that: In S200 , the binder includes an aluminosilicate binder.

5. The preparation method according to claim 4, characterized in that: Every 100 parts by mass of the aluminosilicate binder comprises: Sodium silicate: 30 parts by mass; Sodium aluminate: 25 parts by mass; Kaolin: 20 parts by mass; Potassium hydroxide: 8 parts by mass; Potassium tetraborate: 8 parts by mass; Aluminum hydroxide: 6 parts by mass; Polyacrylamide: 3 parts by mass.

6. The preparation method according to any one of claims 1 to 5, characterized in that In S300, the freeze-drying temperature is -80°C to -45°C, and the drying time is 4h to 8h; and / or In S400, the cold isostatic pressing pressure is 200 MPa to 300 MPa, and the holding time is 5 min to 10 min; and / or In S500, the sintering temperature of the vacuum sintering is 1200° C. to 1400° C., the sintering time is 1 h to 3 h, and the vacuum degree is 0.5×10 -3 Pa to 0.8×10 -3 Pa.

7. The preparation method according to any one of claims 1 to 5, characterized in that In S200, the mixed powder: binder: amino organic modifier is 100: (2-6): (2-3) in mass ratio.

8. The preparation method according to any one of claims 1 to 5, characterized in that In S200, the exposure dose of the ultraviolet light is 1500 mJ / cm 2 Up to 1800mJ / cm 2 , the heating temperature is 60°C to 70°C.

9. The preparation method according to any one of claims 1 to 5, characterized in that: The carboxyl organic modifier includes diethylenetriaminepentaacetic acid dianhydride; the amino organic modifier includes dimethylaminoethyl methacrylate.

10. A zirconia ceramic for ceramic compass pins, characterized in that: The zirconia ceramic is obtained by the preparation method according to any one of claims 1 to 9.